2015
DOI: 10.1016/j.pec.2015.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Do multimorbidity and deprivation influence patients’ emotional expressions and doctors’ responses in primary care consultations? – An exploratory study using multilevel analysis

Abstract: Objective: To explore whether and how patient multimorbidity and socioeconomic deprivation conditions might influence patients' emotional expression and doctors' responses in the general practice (GP) consultations. Results: GPs were less likely to provide space as the consultation proceeded, controlling for multimorbidity and deprivation variables. Patients with multimorbidity were less likely to express emotional distress in an explicit form. GPs were more likely to provide acknowledgement to emotions expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
4
1
Order By: Relevance
“…On the other hand, while most other studies found that cue B (i.e. implications of concern through emphasis, including metaphors and uncommon wordings) was the most common emotional expression (35)(36)(37)(60)(61)(62)(63)(64), cue D (i.e. mentioning of stressful life circumstances without verbal emphasis) was the most common in our study.…”
Section: Discussioncontrasting
confidence: 83%
“…On the other hand, while most other studies found that cue B (i.e. implications of concern through emphasis, including metaphors and uncommon wordings) was the most common emotional expression (35)(36)(37)(60)(61)(62)(63)(64), cue D (i.e. mentioning of stressful life circumstances without verbal emphasis) was the most common in our study.…”
Section: Discussioncontrasting
confidence: 83%
“…[41] The explicitness of responses was assessed in studies with other primary healthcare providers. Nurses interacting with older patients or patients with mild mental health problems and general practitioners mainly responded in a non-explicit providing space way to patients' negative emotions, with brief verbal encouragements as the most common response [21,23,27]. These studies -as well as our study -are in line with the ambitions in healthcare to make consultations more patient-centred instead of provider-centred [12].…”
Section: Discussionsupporting
confidence: 74%
“…This is comparable to the responses of nursing staff to patients' emotional cues during private consultations [20][21][22][23][24][25]. Whereas physicians are less likely to further explore patients' emotional cues, their positive responses vary from 33 to 80% [19,22,24,[26][27][28]. Responding to cues and concerns was perceived challenging for pharmacy staff during consultations at the counter in Dutch pharmacies.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Previous research has attributed differences in healthcare communication to variability in patient and healthcare practitioner demographic, psychological and cultural characteristics [25][26][27]. Multilevel modelling approaches have previously been employed to examine patient-practitioner communication in a variety of clinical settings, including oncology [28], dentistry [29], and primary care [22,30,31].…”
Section: Introductionmentioning
confidence: 99%